Contribution of TRPM8 Channels to Cold Transduction in Primary Sensory Neurons and Peripheral Nerve Terminals - Madrid, Rodolfo (J Neurosci, 2006)
Transient receptor potential melastatin 8 (TRPM8) is the best molecular candidate for innocuous cold detection by peripheral thermoreceptor terminals. To dissect out the contribution of this cold- and menthol-gated, nonselective cation channel to cold transduction, we identified BCTC [N-(4-tert-butylphenyl)-4-(3-chloropyridin-2-yl)piperazine-1-carboxamide] as a potent and full blocker of recombinant TRPM8 channels. In cold-sensitive trigeminal ganglion neurons of mice and guinea pig, responses to menthol were abolished by BCTC. In contrast, the effect of BCTC on cold-evoked responses was variable but showed a good correlation with the presence or lack of menthol sensitivity in the same neuron, suggesting a specific blocking action of BCTC on TRPM8 channels. The biophysical properties of native cold-gated currents (I(cold)), and the currents blocked by BCTC were nearly identical, consistent with a role of this channel in cold sensing at the soma. The temperature activation threshold of native TRPM8 channels was significantly warmer than those reported in previous expression studies. The effect of BCTC on nativeI(cold) was characterized by a dose-dependent shift in the temperature threshold of activation. The role of TRPM8 in transduction was further investigated in the guinea pig cornea, a peripheral territory densely innervated with cold thermoreceptors. All cold-sensitive terminals were activated by menthol, suggesting the functional expression of TRPM8 channels in their membrane. However, the spontaneous activity and firing pattern characteristic of cold thermoreceptors was totally immune to TRPM8 channel blockade with BCTC or SKF96365 (1-[2-(4-methoxyphenyl)-2-[3-(4-methoxyphenyl)propoxy]ethyl-1H-imidazole hydrochloride). Cold-evoked responses in corneal terminals were also essentially unaffected by these drugs, whereas responses to menthol were completely abolished. The minor impairment in the ability to transduce cold stimuli by peripheral corneal thermoreceptors during TRPM8 blockade unveils an overlapping functional role for various thermosensitive mechanisms in these nerve terminals.